Nine- to fourteen-year follow-up of implant treatment. Part II: presence of peri-implant lesions - Ann Marie Roos-Jansa°ker (journal of clinical periodontology, 2006)
Objectives: The aim of this study was to analyse the proportions of peri-implant lesions at implants after 9–14 years of function. Material and Methods: Two hundred and ninety-four patients underwent implant therapy during the years 1988–1992 in Kristianstad County. These individuals were recalled to the speciality clinic 1 and 5 years after placement of the suprastructure. Between 2000 and 2002, 218 patients with 999 implants were examined clinically and radiographically. Results: Forty-eight per cent of the implants had probing depth X4mm and bleeding on probing (peri-implant mucositis). In 20.4% of the implants, the bone level was located 3.1mm apical to the implant shoulder. Progressive bone loss (X1.8 mm) during the observation period was found in 7.7% of the implants. Peri-implantitis defined as bone loss X1.8mm compared with 1-year data (the apical border of the bony defect located at or apical to the third thread, i.e. a minimum of 3.1mm apical to the implant shoulder), combined with bleeding on probing and or pus, were diagnosed among 16% of the patients and 6.6% of the implants. Conclusion: After 10 years in use without systematic supportive treatment, periimplant lesions is a common clinical entity adjacent to titanium implants.